Intracranial Arterial Calcification Relates to Long-Term Risk of Recurrent Stroke and Post-stroke Mortality - Wu, Xiaohong; Bos, Daniel; Ren, Lijie; Leung, Thomas Wai-hong; Chu, Winnie Chiu-Wing; Wong, Lawrence Ka Sing; Abrigo, Jill; Chen, Xiang Yan (Frontiers in Neurology, 2020)
Background: Intracranial arterial calcification (IAC) is highly prevalent in ischemic stroke patients. However, data on the association of IAC with stroke recurrence and mortality remains limited. We examined the effect of IAC on the long-term recurrence of stroke and the risk of post-stroke mortality. Methods: Using a prospective stroke registry, we recruited 694 patients (mean age 71.6±12.4; male sex 50.3%) since December 2004. IAC was visualized using the computed tomography exam that was made at hospital admission and was quantified with the Agatston method. All patients were regularly followed up till July 2016. The impacts of IAC on stroke recurrence and mortality were assessed using Cox-regression models with adjustments for age, sex and relevant cardiovascular risk factors. Results: During a median follow-up period of 8.8 years, 156 patients (22.5%) suffered a recurrent stroke and 84 died (12.1%). We found that a higher IAC Agatston score related to a higher risk of stroke recurrence (HR per 1-SD increase in IAC: 1.30; 95% CI, 1.08-1.56, p=0.005) and a higher risk of post-stroke mortality (HR per 1-SD increase, 1.44; 95% CI, 1.06-1.96, p=0.019). After investigating etiology-specific risks of stroke-recurrence, we found that a higher IAC Agatston score specifically associated with small-vessel occlusive stroke. Conclusions: IAC is a strong risk factor for recurrent stroke and post-stroke mortality. Among stroke subtypes, IAC relates to higher risk of stroke recurrence among patients with small-vessel disease, which indicates chronic calcification detected in large cerebral arteries may have potential effects on the cerebrovascular beds extending to small vessels.